2010
DOI: 10.5483/bmbrep.2010.43.7.499
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the polymorphisms in the thymic stromal lymphopoietin receptor (TSLPR) and their association with asthma

Abstract: The present study aimed to investigate whether the polymorphisms in the TSLPR gene are associated with atopic and asthmatic disease in the Korean population. We identified eleven single nucleotide polymorphisms (SNPs) and two variation sites in the TSLPR gene, including the promoter region. The genotype and allele frequencies of g.33G>C of the TSLPR gene in asthma patients were significantly different from the respective frequencies of the control group (P = 0.006 and 0.003, respectively). Our additional analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Our results suggest that TSLPR polymorphisms are possibly correlated with susceptibility to SLE. We have previously identified 11 SNPs and 2 variation sites in the entire coding region and boundary intron sequences of TSLPR isoform 1, including the ~1.9 kb promoter region, using a direct sequencing method (Yu et al, 2010). However, we have still not comprehensively captured all the diversity in the TSLPR gene, and other associations may still reside at this locus; these associations could not be addressed in the present study.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Our results suggest that TSLPR polymorphisms are possibly correlated with susceptibility to SLE. We have previously identified 11 SNPs and 2 variation sites in the entire coding region and boundary intron sequences of TSLPR isoform 1, including the ~1.9 kb promoter region, using a direct sequencing method (Yu et al, 2010). However, we have still not comprehensively captured all the diversity in the TSLPR gene, and other associations may still reside at this locus; these associations could not be addressed in the present study.…”
Section: Discussionmentioning
confidence: 76%
“…We previously showed by RT-PCR that the expressed levels of TSLPR mRNA were highest in ovary, pancreas, and lung. Additionally, TSLPR mRNA, is only barely detected in kidney, heart, thymus, and testis, and not detected in brain and skeletal muscle (Yu et al, 2010). We identified 11 single-nucleotide polymorphisms (SNPs) and 2 variation sites in the human TSLPR gene, and our data suggested that SNPs in the TSLPR gene are associated with susceptibility to atopic asthma in the Korean population (Yu et al, 2010).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…TSLP also results in the polarization of DCs, which drives the differentiation of naı¨ve T-cells to inflammatory Th2 cells through the up-regulation of co-stimulatory molecules (CD40, CD80), MHC II molecules and OX40 ligand (OX40L). 5,6 OX40L and its receptor (OX40) belong to the superfamily of TNF/ TNF receptor proteins. 7 OX40L is preferentially expressed on APC, such as myeloid and plasmacytoid DCs and B-cells, and may also be expressed on vascular endothelial cells, 8 mast cells 9 and NK cells.…”
Section: Introductionmentioning
confidence: 99%